Effects of Spontaneous Abortion on Women’s Psychological Domain of Quality of Life - fadhil, Sarab; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2013)
Objective: To find out the association between psychological domain of Quality of life with study variable (demographic &reproductive). Methodology: A descriptive Analytical study was conduct on Non-probability (purposive sample)of (200) women who have suffering from spontaneous abortion in maternity unit from four hospitals which include Al-Elwyia maternity teaching hospital, and Baghdad teaching hospital at Al-Russafa sector. Al –karekh maternity hospital and Al-Yarmook teaching hospital at Al-karekh sector. A questionnaire was used as a tool of data collection for the period of February 3rd 2013 to April 26th 2013 and consisted of four parts, including demographic, reproductive characteristics, and psychological domain of quality of life. A pilot study was carried out to test the reliability of the questionnaire and content validity was carried out through the 20 experts. Descriptive statistical analyses were used to analyze the data. Results :The results of the study revealed that (26.5%) of women their age range (25-29) years, (48%) within the normal body weight,(27.5%)graduated from primary school, (25%) of their husband graduated from college or institute, (80%) housewives, (54.5%) of their husband were employee, (48%) within low category of socioeconomic status. And about the reproductive information (66%) of women were primi or multi gravida, and (25%) have previous two delivery, and (52.5%) have previous one abortion, also there are association between psychological domain of quality of life and sociodemographic status(Age groups)at (p=0.006), and with reproductive parameters (gravid) at (p=0.031). Recommendations: The study recommended Conduct Structured Teaching Programmed (STP) to pregnant women’s with history of miscarriage included meaning, causes, and prevention of miscarriage, and Reinforce the role of the psychological care for the women by primary health center. the study recommends to collaborative action can Ministry of Health take in distribution of awareness for women towards the problem by conducting a booklet or lectures about miscarriage.